Pengaruh Patriarki di Sektor Pekerjaan terhadap Hak Pekerja Wanita dalam Konteks Kesetaraan Gender - Kuni Wafiqotuz Zahroh (Tamilis Synex: Multidimensional Collaboration, 2023)
The impact of patriarchal culture creates social inequalities, these social gaps include in the division of labor women are often placed in less strategic positions and are still underestimated. Because in that scope it prioritizes male workers over women, but also they are only used as helpers or only members in management, cannot get an important role. But the employment space there is also justice, which includes the distribution of severance pay and the division of working time, men or women get the same rights, meaning that they are not differentiated between men and women. The relationship between women in the employment space also has an impact, namely the emergence of a double burden by women in the household because these women on the other hand have responsibilities in their work, namely in household chores, because the woman is actually a housewife.